Join the IDNLearn.com community and start finding the answers you need today. Join our interactive Q&A community and access a wealth of reliable answers to your most pressing questions.

Fill in the table using this function rule.

y=-2x+3

× -2, -1, 0, 1


Sagot :

Answer:

If x = -2, -1, 0, 1, then (In this order) y = 7, 5, 3, 1

Step-by-step explanation:

If you put in each value of "x" into the equation, you'll get the appropriate "y".

y= -2(-2)+3

y= 4+3

y= 7

y= -2(-1)+3

y= 2+3

y= 5

y= -2(0)+3

y= 0+3

y= 3

y= -2(1)+3

y= -2+3

y= 1

We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thank you for choosing IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more solutions.